Intellect and Divinisation According to Meister Eckhart - Verdú Berganza, Ignacio (Pensamiento. Revista de Investigación e Información Filosófica, 2012)
This paper revolves around the Eckhartian idea of the «divinisation of man», a matter thatcan be approached from different perspectives and allows the focus of attention on a series of aspectsof Eckhart’s thought (his anthropology, ontology, and Platonism...). The role played by human intellectin the «divinisation process» and its relationship with God understood as intellect are examined accordingto the following points: the mysteries of Incarnation and the Holy Trinity in Eckhart's thought,his proposal on detachment and renunciation (abandonment), the relationship between nothing, One,and Divinity and the possible pantheism of Eckhartian mysticism.
Keywords: divinisation of man; intellect; detachment; renunciation (abandonment); poverty; one; divinity; pantheism and mysticism.